Le théâtre-récit: exemple Marguerite Duras ou l'oralité écrite et l'écrit parlé - Šimková, Soňa (Verbum – Analecta Neolatina, 2005)
The present paper is concerned with the question of the substance of language in the work of Marguerite Duras. Her works can be characterised as a fluid passage between the novel, dramatic text and film script. In the French literature, her theatre work is subsumed under the concept of théâtre-récit, which refers to an uncanonical type of theatre, the theatre of narration rather than direct representation. The author created a specific vision of text presentation which was best fulfilled by the director Claude Régy and Duras herself in her own stagings. In fact, this new and alternative way to text presentation was based on telling and not on showing. By telling the text from a distance, all its orality emerges and plays a main role in the performance - the language of Marguerite Duras being a texture of oral, spoken and written style.